Isolation and Evaluation of Antibacterial Potential Test of Plant Carthamus oxycantha - Amir Hassan; Ibad Ullah; Waqas Ahmad (Journal of Tropical Pharmacy and Chemistry, 2021)
The present investigation was initiated to find a suitable alternative to synthetic antibiotics for the management of diseases caused by bacteria. Carthamus oxycantha.L locally known as wild safflower member of family Asteraceae that grows wildly. The study was conducted using as Agar well diffusion to trace the antibacterial potential for to evaluate the efficiency of ethanolic extract of Carthamus oxycantha with concentration of 05, 10, 15, and 20 mg/ml against gram-positive Staphylococcus aureus and gram-negative Escherichia Coli species and them compared with that of Clindamycin, Ampicillin and Kanamycin (10 mg). Zone of inhibition for the extracts were 10.667 to 20.00 mm as compared to standard drug Clindamycin, Ampicillin and kanamycin (15.00-20.00 mm). Antibacterial assays indicates that Carthamus oxycantha has potential natural antimicrobial agents against E-coli and S. aureus. The findings of the present study suggested that ethanolic extract of C. oxycantha has strong potential to serve as possible antibacterial.